The Strategies Adopted by the Primary School Administrators in Removing the Deficiencies Related to the Education Training State of the Schools - Demirtas, Zulfu; Kahveci, Gokhan (Dergipark Akad, 2015)
This study aimed to define the strategies adopted by primary school principals in order to carry out the recommendations under the status of education and training title in inspection notification. 37 administrators have voluntarily participated in the study as 9 of them are school principals and 28 of them are assistant principals Unstructured interview form is used in the study and What kind of strategies do you pursue to carry out the recommendations made for arranging education-training state of your school? question is directed at participants. Data are analyzed through qualitative techniques such as content analysis. According to the findings of the study primary school administrators adopted four main strategies in order to remove deficiencies in the education state of their schools as: (1) Attendance and cooperation (2) Social, cultural and sportive activities (3) Convenience with the regulations (4) Guidance services.
Keywords: Inspection; Education and Training; Primary; School; Strategy